(untitled) (Research, Society and Development, 2022)
Chronic non- communicable diseases are one of the most prevalent health problems in Brazil correspondin to the vast majority of causes of death. Given this scenario, functional foods and their properties can provide benefits to improve quality of life and reduce the risk of chronic degenerative diseases. The aim of this study was to review the effects of omega 3 fatty acids through functional foods, as well as their specific dosage, in order to provide benefits to human health. Methods: A bibliographic review was carried out using the Google Scholar, Scientific Electronic Library Online (SciELO), U.S. National Library of Medicine (PubMed). Results: Studies have shown that the consumption of omega 3 is extremely important both in the diet of healthy individuals and for those who already have some diseases such as diabetes, systemic arterial hypertension, neurological disorders and cardiovascular diseases in most. Conclusion: An adequate diet helps individuals in the prevention and treatment of non-communicable chronic diseases, especially cardiovascular diseases. Omega 3 showed a reduction in some cardiovascular events, in the context of secondary prevention, but in diabetes no significant benefits were found.